2022
DOI: 10.6004/jnccn.2022.7036
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toxicity and Its Association With Prostate and Colon Cancer Screening

Abstract: Background: The term “financial toxicity” or “hardship” is a patient-reported outcome that results from the material costs of cancer care, the psychological impacts of these costs, and the coping strategies that patients use to deal with the strain that includes delaying or forgoing care. However, little is known about the impact of financial toxicity on cancer screening. We examined the effects of financial toxicity on the use of screening tests for prostate and colon cancer. We hypothesized that greater fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Financial hardship and financial toxicity present substantial barriers to patients’ having a fair and just opportunity to achieve the best health outcomes possible as they try to prevent, find, treat, and survive cancer, as well as implementation challenges to the cancer care delivery system. Such challenges are also present for cancer screening, as research suggests that those experiencing financial hardship are less likely to get prostate and colorectal cancer screenings [ 18 ]. Thus, changes to care delivery will need to be put in place to screen patients for financial hardship before entering cancer care; patients will need to be navigated to the appropriate resources to address the material, psychological, and behavioral components of financial hardship (preferably multiple times as they navigate care); and patients must also be connected to those resources and followed up to ensure that the resources addressed their financial hardship.…”
Section: Discussionmentioning
confidence: 99%
“…Financial hardship and financial toxicity present substantial barriers to patients’ having a fair and just opportunity to achieve the best health outcomes possible as they try to prevent, find, treat, and survive cancer, as well as implementation challenges to the cancer care delivery system. Such challenges are also present for cancer screening, as research suggests that those experiencing financial hardship are less likely to get prostate and colorectal cancer screenings [ 18 ]. Thus, changes to care delivery will need to be put in place to screen patients for financial hardship before entering cancer care; patients will need to be navigated to the appropriate resources to address the material, psychological, and behavioral components of financial hardship (preferably multiple times as they navigate care); and patients must also be connected to those resources and followed up to ensure that the resources addressed their financial hardship.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that more perceived burdens is connected with a role in limiting of receiving colon cancer screening. Budgetary damage can affect both cancer therapy and cancer screening, and healthcare providers ought to be cautious of this (15). Successful focal immunochemical test is connected with heightened incidence of rheumatoid arthritis in the normal community, verifying that gut mucosal abnormalities are linked to the onset of systemic lupus erythematosus, rheumatoid arthritis, and psoriatic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…This comparison is similarly found in prostate cancer, for which the initial PSA screening test is low-cost, with the possibility of additional expenses for further workup (eg, urologic consultation with transrectal ultrasound-guided biopsy). Although Herriges et al 3 did not specifically analyze FOBT/FIT in their financial hardship analysis, other studies have shown that FIT (a cheaper alternative), followed by colonoscopy if the FIT results are positive, increased patient compliance, meeting goals of .80% screening adherence after implementation of a comprehensive approach to screening. 4 Although higher-volume programs can decrease the cost per person for screening colonoscopies, FOBT/FIT followed by diagnostic colonoscopy as needed is cost-effective compared with universal screening colonoscopies ($1,291 vs $3,153).…”
mentioning
confidence: 99%
“…Herriges et al 3 have shown that financial toxicity not only is predominant in cancer care delivery but also impacts cancer screening. The causes of low screening rates are multifactorial; however, financial toxicity unmistakably plays a significant role.…”
mentioning
confidence: 99%